React Router Quick Start Guide: Routing in React Applications Made Easy - Ganatra, Sagar (Packt Publishing, Limited, 2018)
React Router is the routing library for React, and it can be used in both React Web and React Native applications. This book is a simple way to get started with React Router and harness its full power for your applications.